Cryptocurrencies and gold - Similarities and differences - Jens Klose (Philipps-University Marburg, School of Business and Economics, 2021)
This article investigates similarities and differences between gold and four cryptocurrencies (Bitcoin, Ethereum, Bitcoin Cash and Litecoin). To do so, we estimate a system-GARCH-in-mean with respect to four determinants for the period starting 7/18/2014 at earliest until 7/12/2021. We find that, first, liquidity premia are less important. Second, volatility premia exist in either gold and cryptocurrencies. Third, the response of cryptocurrencies to ex- change rate changes is more pronounced than for gold at least if developing countries are included. Fourth, gold exhibits a safe haven status, while cryp- tocurrencies do not. So those cannot be seen as a store of value but rather as speculative assets.
Keywords: E42; G15; C58; 330; Cryptocurrencies; Gold; System-GARCH-in-mean